(untitled) (Third Sector Social Economic Review, 2021)
One of the most important elements that form the state is the land. For this reason, real estate management is one of the most important issues that have maintained its importance for centuries. In this study, the subject of real estate management, which has preserved its importance from the past to the present, is discussed, and the way in which the records of the real estate in our country were preserved in the past, the current situation and the latest developments are examined. These records, which also shape our social life today, are scanned and transferred to digital media within the scope of the TARBİS project, a digital transformation project of the General Directorate of Land Registry and Cadastre (TKGM). In the study, the practices and principles of real estate management from the past to the present are discussed and evaluated in detail, and the steps taken by TKGM on the path of digitalization are included, the gaps in this area are mentioned and future suggestions are presented. As a result of the study, it was concluded that TKGM, whose foundations were laid with the Republican Period, took very important steps towards digitalization and that these steps should be developed in the light of developments in technology, adapted to automatic systems by minimizing human interaction and carried forward.